Domestic Mass Shooters: The Association With Unmedicated and Untreated Psychiatric Illness. Issue 4 (July 2021) - Glick, Ira D.; Cerfolio, Nina E.; Kamis, Danielle; Laurence, Michael
Abstract: Background: Given the relative lack of psychiatric information and data on the perpetrators of US mass shootings, the aim of our study was to understand who these "mass shooters" were and whether they had a psychiatric illness. If so, were they competently diagnosed, and if so, were they treated with appropriate medication for their diagnoses before the violence? Methods: Because a prospective study of diagnosis and treatment could not, for obvious reasons, be carried out, we designed a retrospective, observational study of mass shooters, defined as those who killed 4 or more people with firearms between 1982 and 2012 or who killed 3 or more people with firearms between 2013 and 2019 in the United States. We used the Mother Jones database—a database of 115 persons identified as committing a mass shooting in the United States between January 1982 and September 2019. In the vast majority of the incidents identified in the database, the perpetrator died either during or shortly after the crime, leaving little reliable information about their history—especially psychiatric history. We focused on the 35 mass shooters who survived and for which legal proceedings were instituted because these cases presented the most reliable psychiatric information. For each of these 35 mass shootings, we interviewed forensic psychiatrists and forensic psychologists who examined the perpetrator after the crime and/or collected the testimony and reports by psychiatrist(s) at trial or in the postconviction proceedings contained in the court record. In addition, we reviewed available information from the court proceedings, public records, a videotaped interview of assailant by law enforcement, social media postings of the assailant, and writings of the assailant. After collecting the clinical information from multiple sources on each case to make a Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, diagnosis, we also completed a Sheehan Diagnostic Scale. After this, 20 additional cases where the assailant died at the crime were randomly selected form the remaining 80, to determine whether there were differences in psychiatric diagnoses and treatment between such assailants and those who survived. Results: Twenty-eight of 35 cases in which the assailant survived had a psychiatric diagnosis—18 with schizophrenia, 3 with bipolar I disorders, 2 with delusional disorders, persecutory type, 2 with personality disorders (1 paranoid and 1 borderline), 2 with substance-related disorders without other psychiatric diagnoses, and 1 with posttraumatic stress disorder. Four had no psychiatric diagnosis, and in 3, we did not have enough information to make a diagnosis. Of 15 of 20 cases in which the assailant died, 8 had schizophrenia. None of those diagnosed with psychiatric illnesses were treated with medication. Conclusions: A significant proportion of mass shooters experienced unmedicated and untreated psychiatric disorder.